Karl Polanyi and the Problem of Corporate Social Responsibility - Moncrieff, Lilian (Journal of Law and Society, 2015)
This article considers Corporate Social Responsibility (CSR) as part of the projects in ‘new governance and decentred regulation’, which draw social forces towards the regulation of economic behaviour. It uses Karl Polanyi to open up pertinent interfaces between society and economy for observation, and Gunther Teubner to substantiate a ‘regulatory’ view of the company's social relationships. The article finds that CSR combines movements for the recognition of social relationships, on an unprecedented scale, with rigorous simultaneous movements for market building and social abstraction. Twenty-first-century market economy is defined by a capacity to contain ‘the social,’ which is thrown between the two movements, creating opportunities for companies to void the market's social limits. The article counterposes that the social that ‘returns’ after marketization needs to find its way past market-building CSR, to constructively unshackle and redefine the framing of social conflicts that concern the corporation.
Law; Sociology
Keywords: CSR; corporate social responsibility; marketization